Reconstruction of Physical Correlations Using Symbolic Regression - Stautner, Stautner; Weinert, Klaus (Universität Dortmund, 2002)
Modeling the particle ow mechanisms in orthogonal cutting of turning processes is a vital task in mechanical engineering. This paper presents a new approach that differs from techniques like finite element analyzes (FEA) or molecular dynamics (MD). Using symbolic regression, a genetic programming system evolves mathematical formulae that describe the trajectories of single particles of steel recorded during the turning process by a high-speed camera.
Reihe Computational Intelligence ; 116
Keywords: 004